Burned - Shepard, Sara, 1977- (New York : HarperTeen, 2012)
The girls embark on a cruise vacation away from Rosewood, but trouble follows and new secrets are formed as Emily gets friendly with a stowaway, Aria goes treasure-hunting, Spencer goes overboard for a crush, and Hanna is reunited with someone from the past.
Young Adult.
Young Adult
Keywords: Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Ocean travel -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Fiction; Friendship -- Fiction; Mystery and detective stories; Ocean travel -- Fiction; Secrecy -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; Mystery fiction; Ocean travel -- Fiction; Secrecy -- Fiction; Mystery fiction